The effect of the guided discovery learning model on students' mathematical reasoning ability - Reni Auliana Amri; Pentatito Gunowibowo; Agung Putra Wijaya (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This quasi-experimental study aimed to investigate the effect of the Guided Discovery Learning (GDL) model on the mathematical reasoning ability of eighth-grade students. The population consisted of 319 students from Grade VIII at SMP Negeri 20 Bandar Lampung during the 2024/2025 academic year, distributed across ten classes (VIII-A to VIII-J). Using a purposive sampling technique, two classes were selected as research samples: class VIII-B (32 students) as the experimental group, which received instruction using the GDL model, and class VIII-A (32 students) as the control group, which received conventional cooperative learning. The study employed a pretest-posttest control group design. The research data were quantitative, obtained through a mathematical reasoning ability test on the topic of Systems of Linear Equations in Two Variables, administered before and after the intervention in both groups. Statistical analysis using an independent samples t-test on the gain scores revealed a statistically significant difference. The findings showed that students in the GDL group experienced greater improvement in mathematical reasoning ability compared to those in the control group. These results suggest that the GDL model has a positive and significant effect on enhancing students' mathematical reasoning skills.